Development and psychometric analysis of the PROMIS pain behavior item bank - Dennis A. Revicki; Wen-Hung Chen; Neesha Harnam; Karon F. Cook; Dagmar Amtmann; Leigh F. Callahan; Mark P. Jensen; Francis J. Keefe (2009)
The measurement of pain behavior is a key component of the assessment of persons with chronic pain; however, few self-reported pain behavior instruments have been developed. We developed a pain behavior item bank as part of the Patient-Reported Outcome Measurement Information System (PROMIS). For the Wave I testing, because of the large number of PROMIS items, a complex sampling approach was used where participants were randomly assigned to either respond to two full-item banks or to multiple 7-item blocks of items. A web-based survey was designed and completed by 15,528 members of the general population and 967 individuals with different types of chronic pain. Item response theory (IRT) analysis models were used to evaluate item characteristics and to scale both items and individuals on the pain behavior domain. The pain behavior item bank demonstrated good fit to a unidimensional model (Comparative Fit Index = 0.94). Several iterations of IRT analyses resulted in a final 39-item pain behavior bank, and different IRT models were fit to the total sample and to those participants who experienced some pain. The results indicated that these items demonstrated good coverage of the pain behavior construct. Pain behavior scores were strongly related to pain intensity and moderately related to self-reported general health status. Mean pain behavior scores varied significantly by groups based on pain severity and general health status. The PROMIS pain behavior item bank can be used to develop static short-form and dynamic measures of pain behavior for clinical studies.